Calibración de las ecuaciones de velocidad en la vía LojaCatamayo - Alverca Maza, Edgar Fabricio (2018)
Abstract:The consistency analyzes check the differences in speeds between elements of the road (for example, straight - curve). During the design phase, these analyzes are carried out using speed prediction models, which have not yet been calibrated for two-lane rural roads in Ecuador. This research presents speed models for two-lane mountain roads according to geographical, geometric and local driving styles. To this end, an experimental plan was drawn up based on previous research. Speed data were collected through GPS continuous measurement devices (Video VBOX), and operating speed profiles were obtained. Finally, the models were developed based on the radius of curvature, length of the line and the longitudinal slope of the path using statistical methods. These models were calibrated and validated by comparing the observed and estimated values. With these models, road designers and inspectors can evaluate the safety that this type of road offers and, if necessary, propose modifications to the layout.